High-frequency low-loss MnZn ferrite material as well as preparation method and application thereof

By adding perovskite cobalt oxide LaCoO3 to the MnZn ferrite material to form a high resistance layer, the problem of high loss at high frequencies of MnZn ferrite material is solved, and a significant reduction in loss and improvement in performance is achieved.

CN119912250APending Publication Date: 2025-05-02SHANDONG UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510091593.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing MnZn ferrite materials have high losses at high frequencies, making it difficult to meet the needs of MHz frequency applications.

Method used

Perovskite cobalt oxide LaCoO3 is used as a new additive, and a high resistance layer is formed by adding LaCoO3 to improve grain boundary resistivity, refine grains, and reduce eddy current losses and hysteresis losses.

Benefits of technology

The loss of MnZn ferrite material under 1MHz, 30mT and 25℃ is significantly reduced, reaching 143mW/cm3, improving the performance of the material at high frequencies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912250A_ABST
    Figure CN119912250A_ABST
Patent Text Reader

Abstract

The invention relates to a high-frequency low-loss MnZn ferrite material as well as a preparation method and application thereof. The high-frequency low-loss MnZn ferrite material comprises main components and auxiliary components, the main components comprise the following components in mole percent: 50-54 mol% of Fe2O3, 34-38 mol% of Mn3O4 and 10-14 mol% of ZnO, and the total amount is 100 mol%; and the auxiliary components comprise the following components in percentage by mass in the main components: 1000 to 1400 ppm of Ta2O5, 200 to 600 ppm of CaO and 1000 to 1400 ppm of LaCoO3. The invention also provides a preparation method and application of the MnZn ferrite material. According to the invention, the perovskite type cobalt oxide LaCoO3 is applied to preparation of the MnZn power ferrite for the first time, and LaCoO3 is added, so that La < 3 + > ions in LaCoO3 form a high-resistance layer at a grain boundary, the grain boundary resistivity is improved, the grain boundary is obvious, grains are refined, and eddy current loss and residual loss are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel high-frequency low-loss MnZn ferrite material and a preparation method and application thereof, belonging to the technical field of ferrite material preparation. Background Art

[0002] With the continuous development and innovation in the application field of electronic components, higher requirements are placed on electronic components and their constituent materials. Electronic components as a whole tend to be miniaturized, high-frequency, and efficient, which requires that its important component material MnZn ferrite can have excellent performance at high frequencies, especially high-frequency losses must be controlled, so that electronic components can improve efficiency, reduce heat, extend service life, and maintain good working conditions in high-frequency working conditions. Therefore, it is of great significance to develop a low-loss MnZn power ferrite at MHz frequencies. At present, many research teams have proposed different methods to reduce the high-frequency loss of MnZn ferrite, such as optimizing the preparation process and doping with different types of additives, but the types of dopants are mostly concentrated in transition metal oxides and several rare earth metal oxides.

[0003] Chinese patent document CN116813320A discloses a MnZn ferrite material and its preparation method. The invention adds doped SiO2, CaCO3, and LiBO2 to make the loss of MnZn ferrite at 1MHz, 30mT, and in the temperature range of 25℃ to 140℃ be 385~664kW / m 3 Although this material reduces the loss of MnZn ferrite in MHz frequency and wide temperature range, the loss is still relatively high for MHz frequency applications, which is far behind the international leading level.

[0004] Therefore, it is of great significance to find and develop a new additive to make the MnZn ferrite material have lower loss under MHz frequency conditions for its application at high frequencies. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a new high-frequency low-loss MnZn ferrite material and its preparation method and application. Specifically, perovskite-type cobalt oxide LaCoO3 is applied as a new additive to the preparation of MnZn ferrite to improve the performance of MnZn ferrite and help reduce its loss at high frequencies.

[0006] The technical solution of the present invention is as follows:

[0007] A high-frequency low-loss MnZn ferrite material, comprising a main component and an auxiliary component;

[0008] The main components, in terms of molar percentage, include: Fe2O3 50-54mol%, Mn3O4 34-38mol%, ZnO10-14mol%, with a total amount of 100mol%;

[0009] The mass content of the auxiliary components in the main components is: Ta2O5 1000-1400ppm, CaO 200-600ppm, LaCoO3 400-1600ppm.

[0010] Preferably, according to the present invention, the main components, in terms of molar percentage, include: Fe2O3 50-54mol%, Mn3O4 34-38mol%, ZnO 10-14mol%, with a total amount of 100mol%;

[0011] The mass content of the auxiliary components in the main components is: Ta2O5 1100-1300ppm, CaO 300-500ppm, LaCoO3 1100-1300ppm.

[0012] The method for preparing the above-mentioned high-frequency low-loss MnZn ferrite material comprises the following steps:

[0013] (1) weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, performing a ball milling treatment, and then drying the ball milled slurry to obtain the main component powder;

[0014] (2) pre-calcining the main component powder obtained in step (1), and cooling it to obtain a main component pre-calcined material;

[0015] (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, CaO, and LaCoO3 according to the proportion, performing a secondary ball milling treatment, and then drying the ball milled slurry to obtain a mixed powder;

[0016] (4) adding a polyvinyl alcohol aqueous solution to the mixed powder obtained in step (3), uniformly granulating the mixed powder in a mechanical granulator, and sieving the mixed powder to obtain a granular material;

[0017] (5) The granular material obtained in step (4) is pressed and sintered in sequence to obtain a high-frequency and low-loss MnZn ferrite material.

[0018] Preferably, according to the present invention, in step (1), the primary ball milling is carried out in a ball mill, the ball milling time is 60 to 70 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 3:1:1, and the speed of the ball mill is 280 to 320 rpm.

[0019] Preferably according to the present invention, in step (1), the average particle size of the main component powder is ≤1.1 μm.

[0020] Preferably according to the present invention, in step (2), the pre-firing temperature is 900-1000° C. and the time is 1.5-2.5 hours.

[0021] Preferably, according to the present invention, in step (3), the secondary ball milling is carried out in a ball mill, the ball milling time is 300 to 400 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 5:1:1, and the ball mill speed is 330 to 370 rpm.

[0022] Preferably according to the present invention, in step (3), the average particle size of the mixed powder is 1 to 1.2 μm.

[0023] Preferably, according to the present invention, in step (4), the mass concentration of the polyvinyl alcohol aqueous solution is 3-5%, and the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is (5-10):100.

[0024] Preferably according to the present invention, in step (4), the granulation time is 100 to 200 seconds, and the granulation rotation speed is 5000 to 6000r.

[0025] Preferably according to the present invention, in step (5), the pressing is performed at 400 MPa to form a magnetic ring.

[0026] Preferably according to the present invention, in step (5), the sintering is to sinter the magnetic ring at 1150-1200° C. for 25-35 minutes and then cool it to below 300° C.

[0027] Further preferably, the sintering is to sinter the magnetic ring at 1180° C. for 30 minutes.

[0028] The above-mentioned high-frequency low-loss MnZn ferrite material is used in the fields of aerospace or automotive electronics.

[0029] Anything not described in detail in the present invention can be carried out according to the prior art.

[0030] Technical features and beneficial effects of the present invention:

[0031] 1. The present invention proposes for the first time to use a new additive perovskite-type cobalt oxide LaCoO3 in the preparation of MnZn power ferrite. By adding LaCoO3, La 3+ The ions form a high resistance layer at the grain boundary, which increases the grain boundary resistivity, makes the grain boundary obvious, refines the grains, and reduces eddy current loss and residual loss. 3+ The addition of can compensate the anisotropy constant and magnetostriction coefficient of ferrite to make them tend to 0, and then through La 3+ and Co 3+The synergistic effect increases the operating frequency and reduces eddy current loss and hysteresis loss.

[0032] 2. The high-frequency low-loss MnZn ferrite material provided by the present invention greatly improves the performance of MnZn ferrite at high frequencies. Under the test conditions of 1MHz, 30mT, and 25°C, the loss is 143mW / cm 3 , is a potential material that can be used in the MHz-level high-frequency field, and has opened up the application of LaCoO3 in magnetic materials. And due to the addition of Ta2O5, CaO, and LaCoO3, the grain size is reduced, which helps to reduce the total loss. The addition of multiple ions changes the microscopic composition of ferrite materials, changes the electromagnetic properties of materials, and is conducive to reducing losses, providing a new idea and new method for the research and development of magnetic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The XRD diagrams of the MnZn ferrites prepared in Example 1 and Comparative Examples 1-3 of the present invention are shown.

[0034] Figure 2 This is a cross-sectional morphology of the MnZn ferrite material prepared in Example 1.

[0035] Figure 3 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 1.

[0036] Figure 4 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 2.

[0037] Figure 5 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0038] The present invention is further described below by specific examples and drawings, but the scope of the present invention is not limited. The raw materials used in the examples are all conventional raw materials, and the equipment used is all conventional equipment, which can be purchased from the market.

[0039] Example 1

[0040] A high-frequency low-loss MnZn ferrite material, comprising a main component and an auxiliary component;

[0041] The main components, in terms of molar percentage, include: Fe2O3 52mol%, Mn3O4 36mol%, ZnO 12mol%, with a total amount of 100mol%;

[0042] The mass contents of the auxiliary components in the main components are: Ta2O5 1200ppm, CaO 400ppm, LaCoO3 1200ppm.

[0043] The method for preparing the above-mentioned high-frequency low-loss MnZn ferrite material comprises the following steps:

[0044] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they were ball-milled in a ball mill for 65 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water was 3:1:1, and the speed of the ball mill was 300 rpm; then the ball-milled slurry was dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;

[0045] (2) pre-calcining the main component powder obtained in step (1) at 950° C. for 2 hours and naturally cooling the main component pre-calcined material;

[0046] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, CaO, and LaCoO3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 350 minutes. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 350 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;

[0047] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;

[0048] (5) The granular material obtained in step (4) is pressed into a 26*16*5 mm magnetic ring green body at 400 MPa, and then the magnetic ring green body is sintered at 1180° C. for 30 minutes. When the furnace temperature is cooled to below 300° C., the magnetic ring is taken out to obtain a high-frequency and low-loss MnZn ferrite material.

[0049] Example 2

[0050] A high-frequency low-loss MnZn ferrite material, comprising a main component and an auxiliary component;

[0051] The main components, in terms of molar percentage, include: Fe2O3 54mol%, Mn3O4 34mol%, ZnO 12mol%, with a total amount of 100mol%;

[0052] The mass contents of the auxiliary components in the main components are: Ta2O5 1000ppm, CaO 400ppm, LaCoO3 1400ppm.

[0053] The method for preparing the above-mentioned high-frequency low-loss MnZn ferrite material comprises the following steps:

[0054] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they were ball-milled in a ball mill for 60 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water was 3:1:1, and the speed of the ball mill was 320 rpm; then the ball-milled slurry was dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;

[0055] (2) pre-calcining the main component powder obtained in step (1) at 900° C. for 1.5 hours and naturally cooling the main component pre-calcined material;

[0056] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, CaO, and LaCoO3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 300 minutes. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 370 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;

[0057] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;

[0058] (5) The granular material obtained in step (4) is pressed into a 26*16*5 mm magnetic ring green body at 400 MPa, and then the magnetic ring green body is sintered at 1180° C. for 30 minutes. When the furnace temperature is cooled to below 300° C., the magnetic ring is taken out to obtain a high-frequency and low-loss MnZn ferrite material.

[0059] Example 3

[0060] A high-frequency low-loss MnZn ferrite material, comprising a main component and an auxiliary component;

[0061] The main components, in terms of molar percentage, include: Fe2O3 50mol%, Mn3O4 38mol%, ZnO 12mol%, with a total amount of 100mol%;

[0062] The mass contents of the auxiliary components in the main components are: Ta2O5 1400ppm, CaO 400ppm, LaCoO3 1000ppm.

[0063] The method for preparing the above-mentioned high-frequency low-loss MnZn ferrite material comprises the following steps:

[0064] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 70 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 280 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;

[0065] (2) pre-calcining the main component powder obtained in step (1) at 800° C. for 2.5 hours and naturally cooling the main component pre-calcined material;

[0066] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, CaO, and LaCoO3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 400 minutes. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 330 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;

[0067] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;

[0068] (5) The granular material obtained in step (4) is pressed into a 26*16*5 mm magnetic ring green body at 400 MPa, and then the magnetic ring green body is sintered at 1180° C. for 30 minutes. When the furnace temperature is cooled to below 300° C., the magnetic ring is taken out to obtain a high-frequency and low-loss MnZn ferrite material.

[0069] Comparative Example 1

[0070] A MnZn ferrite material, whose specific composition and preparation method are as described in Example 1, except that the auxiliary component does not contain LaCoO3.

[0071] Comparative Example 2

[0072] A MnZn ferrite material, whose specific composition and preparation method are as described in Example 1, except that it does not contain auxiliary components.

[0073] Comparative Example 3

[0074] A MnZn ferrite material, whose specific composition and preparation method are as described in Example 1, except that the auxiliary components are Ta2O5 1200ppm, CaO 400ppm, La2O3 600ppm and Co2O3 600ppm.

[0075] Test example

[0076] 1. XRD characterization and loss (P cv ) test, the results are shown in Table 1 and Figure 1 shown.

[0077] The specific test method is: using a soft magnetic AC measuring instrument (MAST-3000SA) to test the loss P of the products prepared in Example 1 and Comparative Examples 1 to 3 at 1MHz, 30mT, and 25°C cv .

[0078] Table 1. Product performance of Example 1 and Comparative Examples 1 to 3

[0079]

[0080] Depend on Figure 1 It can be seen that the samples prepared in Example 1 of the present invention and Comparative Examples 1 to 3 have only one physical phase, MnZn ferrite, after XRD detection, indicating that the preparation method provided by the present invention can successfully prepare MnZn ferrite material.

[0081] As shown in Table 1, compared with Comparative Examples 1 to 3, the loss of the high-frequency low-loss MnZn ferrite material prepared in Example 1 is significantly reduced under the test conditions of 1 MHz and 30 mT, and in Example 1, it is even reduced to 143 mW·cm -3 This shows that the preparation method provided by the present invention improves the performance of the MnZn ferrite material by controlling the appropriate sintering process and selecting effective dopants, so that the high-frequency and low-loss MnZn ferrite material prepared by the present invention takes into account the characteristics of high frequency and low loss, and solves the problem of high high-frequency loss of conventional MnZn ferrite materials.

[0082] That is, the high-frequency low-loss MnZn ferrite material prepared in Example 1 uses LaCoO3 as an auxiliary component to modify the MnZn ferrite. 3+ The ions form a high resistance layer at the grain boundary, which increases the grain boundary resistivity, makes the grain boundary obvious, refines the grains, and reduces the eddy current loss and residual loss. 3+The addition of can compensate the anisotropy constant and magnetostriction coefficient of ferrite to make them tend to 0, increase the use frequency, and reduce eddy current loss and hysteresis loss. And by comparing Example 1 with Comparative Example 3, it can be found that although Comparative Example 1 introduces La by adding La2O3 and Co2O3 3+ ions and Co 3+ ions, but the introduction effect is obviously not as good as LaCoO3 in Example 1. The effect of reducing eddy current loss and hysteresis loss in Example 1 is obviously better than that in Comparative Example 3.

[0083] 2. The morphology of the products prepared in Example 1 and Comparative Examples 1 to 3 was observed using a scanning electron microscope (SEM). The results are as follows: Figures 2 to 5 shown.

[0084] Depend on Figures 2 to 5 It can be seen that the grain size of the MnZn ferrite material prepared in Example 1 is smaller than that of Comparative Examples 1 and 3, and is significantly smaller than that of Comparative Example 2. This is because the addition of LaCoO3 further reduces the grain size compared with Comparative Example 1, which helps to reduce the total loss, and Co 3+ Ions and La 3+ The addition of ions changes the microscopic composition of ferrite materials and the electromagnetic properties of the materials, which is beneficial to reducing losses.

[0085] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify or replace the technical solution of the present invention with equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A high-frequency, low-loss MnZn ferrite material, characterized in that: Includes main components and auxiliary components; The main components, in terms of molar percentage, include: Fe2O3 50-54mol%, Mn3O4 34-38mol%, ZnO10-14mol%, with a total amount of 100mol%; The mass content of the auxiliary components in the main components is: Ta2O5 1000-1400ppm, CaO 200-600ppm, LaCoO3 1000-1400ppm.

2. The high-frequency low-loss MnZn ferrite material according to claim 1, characterized in that: The main components, in terms of molar percentage, include: Fe2O3 50-54mol%, Mn3O4 34-38mol%, ZnO 10-14mol%, with a total amount of 100mol%; The mass content of the auxiliary components in the main components is: Ta2O5 1100-1300ppm, CaO 300-500ppm, LaCoO3 1100-1300ppm.

3. The method for preparing the high-frequency low-loss MnZn ferrite material according to claim 1 comprises the following steps: (1) weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, performing a ball milling treatment, and then drying the ball milled slurry to obtain the main component powder; (2) pre-calcining the main component powder obtained in step (1), and cooling it to obtain a main component pre-calcined material; (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, CaO, and LaCoO3 according to the proportion, performing a secondary ball milling treatment, and then drying the ball milled slurry to obtain a mixed powder; (4) adding a polyvinyl alcohol aqueous solution to the mixed powder obtained in step (3), uniformly granulating the mixed powder in a mechanical granulator, and sieving the mixed powder to obtain a granular material; (5) The granular material obtained in step (4) is pressed and sintered in sequence to obtain a high-frequency and low-loss MnZn ferrite material.

4. The preparation method according to claim 3, characterized in that: In step (1), the primary ball milling is carried out in a ball mill for 60 to 70 minutes. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 3:1:1, and the speed of the ball mill is 280 to 320 rpm. The average particle size of the main component powder is ≤1.1 μm.

5. The preparation method according to claim 3, characterized in that: In step (2), the pre-firing temperature is 900-1000° C. and the pre-firing time is 1.5-2.5 hours.

6. The preparation method according to claim 3, characterized in that: In step (3), the secondary ball milling is carried out in a ball mill, the ball milling time is 300 to 400 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 5:1:1, and the ball mill speed is 330 to 370 rpm; the average particle size of the mixed powder is 1 to 1.2 μm.

7. The preparation method according to claim 3, characterized in that: In step (4), the mass concentration of the polyvinyl alcohol aqueous solution is 3-5%, and the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is (5-10):

100.

8. The preparation method according to claim 3, characterized in that: The granulation time is 100 to 200 seconds, and the granulation rotation speed is 5000 to 6000 r.

9. The preparation method according to claim 3, characterized in that: In step (5), the pressing is performed at 400 MPa to form a magnetic ring; the sintering is performed by placing the magnetic ring in a sintering device, sintering it at 1150-1200° C. in a mixed gas of 3.5% O2+96.5% N2 for 25-35 minutes, and then cooling it to below 300° C.; Further preferably, the sintering is to sinter the magnetic ring at 1180° C. for 30 minutes.

10. Application of the high-frequency, low-loss MnZn ferrite material according to claim 1 or claim 2 in the fields of aerospace or automotive electronics.

Citation Information

Patent Citations

  • MnZn ferrite for MHz frequency

    CN116813320A